2007
DOI: 10.1093/humrep/dem063
|View full text |Cite
|
Sign up to set email alerts
|

Legislated right for donor-insemination children to know their genetic origin: a study of parental thinking

Abstract: There was a discrepancy between the intentions of the legislation and how parents act in relation to them. To improve compliance, it is crucial to organize education, support and ethical discussion among professionals, and to offer parents, and parents-to-be, counselling, support and group sessions with other DI families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
18

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 25 publications
4
67
0
18
Order By: Relevance
“…In Sweden, physicians have the main responsibility for assessing the suitability of donors and recipients, including ensuring that recipient couples will tell offspring about their genetic origin. Despite this, a recent Swedish study of parents following DI [6] showed that a majority had not been encouraged by the staff involved in the DI treatment to be open about the donation with their child/ren, but had received unclear and contradictory advice regarding disclosure. In a study from the US [7], physicians were the only group of health professionals who encouraged or supported non-disclosure for couples who conceived using gamete donor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, physicians have the main responsibility for assessing the suitability of donors and recipients, including ensuring that recipient couples will tell offspring about their genetic origin. Despite this, a recent Swedish study of parents following DI [6] showed that a majority had not been encouraged by the staff involved in the DI treatment to be open about the donation with their child/ren, but had received unclear and contradictory advice regarding disclosure. In a study from the US [7], physicians were the only group of health professionals who encouraged or supported non-disclosure for couples who conceived using gamete donor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, o país promoveu alterações nos métodos de recrutamento, como a recomendação de que caso o doador fosse casado houvesse o consentimento da esposa sobre a decisão. Segundo Lalos et al(2003), os doadores passaram a ser homens na faixa etária de 34 a 40 anos, casados, com filhos, motivados pelo desejo de ajudar casais inférteis que não conseguem conceber. Anteriormente, predominava no perfil de doadores estudantes universitários que utilizavam a doação para financiar os estudos.…”
Section: A Abolição Do Anonimato: Os Direitos Da Criança Concebidaunclassified
“…A principal alegação referida foi "desnecessário" e "receio de ferir a criança". O estudo realizado por Lalos et al (2007), conduzido entre famílias que fizeram uso de doador de sêmen, revelou que 61% falaram ao filho sobre o processo de concepção, mas 61% não abordaram a possibilidade de o doador ser identificado.…”
Section: Considerações Finaisunclassified
“…Gottlieb et al had not yet told their children about the possibility of ident?jj'ing the donor (Lalos, Gottlieb and Lalos, 2007). And, as reported in Chapter Four, a recent UK study found that, despite the greater encouragement towards disclosure in recent years, less than 8 per cent of egg donation parents and less than 5 per…”
Section: Disclosurementioning
confidence: 99%
“…The research evidence identifies three main reasons for secrecy: first, that couples may view the decision not to disclose as protecting them from negative societal reactions, and preventing their child being considered different from others (Lalos, Gottlieb and Lalos, 2007;Nachtigall et al, 1997); second, that male partners may have concerns that the acknowledgement of infertility would cause their masculinity to come under suspicion (Courtenay, 2000;Glover et al, 1996;Miall, 1996;Nachtigall, Becker and Wozny, 1992); and third, that family relationships (particularly father-child) would be damaged if the child's real genetic identity was revealed (Gottlieb, Lalos and Lindblad, 2000;Lalos, Gottlieb and Lalos, 2007). I found that the users of Repromed express similar concerns.…”
mentioning
confidence: 99%